Tactical behaviour differences of high and low-performing youth soccer players in small-sided and conditioned games - Correia da Silva, D.; Calábria Lopes, M.; González-Víllora, S.; Sarmento, H.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to compare the quantity and quality of tactical actions of high- and low-performing players in two small-sided and conditioned games: (1) standard 3v3 plus goalkeepers, featuring equality for both teams, and; (2) numerical superiority in the offensive phase with two joker players inside the playing field. Fifty-one Under-15 soccer players who performed 8,267 tactical actions were evaluated with the use of the System of Tactical Assessment in Soccer (FUT-SAT). Descriptive statistics, Kolmogorov-Smirnov, t-student, Wilcoxon and Cohen`s kappa tests were applied (p < 0.05) using the SPSS, version 20.0. The high-performing players performed more actions inside the centre of play and low-performing players only increased actions outside the centre of play. Playing with jokers also made the high-performing players increase the total amount of offensive and defensive tactical actions whilst the low-performing players only performed more defensive tactical actions. It was concluded that high-performing players adapt better their positions and their movements on situational demands of the game, performing more offensive and defensive actions closer to the ball carrier. On the other hand, low-performing players performed more actions in spaces further from the centre of play, in both the offensive and defensive phase.